Hydrothermal Syntheses of Colloidal Carbon Nanospheres from Glucose - Shi, L.; Liu, W.; Gou, G.Z.; Wang, Z.F. (Asian Journal of Chemistry, 2015)
Colloidal carbon nanospheres have been prepared from aqueous solutions of glucose in closed systems under hydrothermal conditions. The approach is an absolute 'green' method and the synthetic procedure involves none of the organic solvents, initiators or surfactants that are commonly used for the preparation of nanospheres. The effective reaction temperature on carbon nanospheres diameter was investigated. The obtained nanomaterials were characterized by SEM and FTIR. We find that the diameter of carbon nanospheres increasing with the rise of temperature. Most importantly, the as-formed colloidal carbon nanospheres inherit large numbers of functional groups from the starting materials and have reactive surfaces, which expand the applications fields for both fundamental study and in technical applications.